Analysis of Traffic Accidents Characteristics in Rural Roads of Riau Province - Khairul Fahmi; Jamaludin Mat; Muhidin Bin Arifin (Aptek, 2020)
The study aims to analyze the characteristics of traffic accidents rural roads in Riau Province. The data was obtained from Directorate of Traffic of the Riau Police from year 2014 to 2018. Statistical analyze were conducted using the SPSS software version 20. Mann-whitney and Kruskal Walls analysis were used to analyze the data. There was no significant difference in the number of victims seen from the aspect of the gender of the vehicle that was hit. Based on the the road geometry, there were significant differences in the number of victims, speed, and density of traffic flows. There were significant differences in the traffic speed and density, the number of victims is not significantly different. There were significant differences in traffic speed and density based on road surface conditions, but the number of victims was not significantly different. Based on the pavement conditions, there was no significant difference in density and the number of victims. While, there was a significant difference on vehicle speed. Based on weather conditions, there was no difference in traffic density and the number of victims, but significantly different in terms of speed. Based on the type of road shoulder, there are differences in speed, traffic density, and the number of victims. There are significant differences in speed, traffic density, and the number of victims on the three observed lines. Rantau Berangin- Pasir Pengaraian route was lower than the speed in the other two routes. The average ADT rating for each group on Pekanbaru- Teluk Kuantan route was lower than the vehicle speed on the other two lines. The average rating for each number of victims per group, on Rantau Berangin- Pasir Pengaraian route, was lower than the speed on the other two routes. There are significant differences in speed, traffic density and the number of victims on the three observed lines